Flu-like pandemics and metaphor pre-covid: A corpus investigation. (June 2021) - Taylor, Charlotte; Kidgell, Jasmin
Abstract: The use of metaphor in framing COVID-19 has already attracted considerable attention in both academic and public debate and we have seen extensive discussion of how this pandemic might be compared to past events, such as the so-called 'Spanish flu' of the 1910s. In this paper, we draw these two strands of metaphoric framing and historical comparison together by identifying the metaphorical framings of past influenza pandemics in media and political discourse in the UK over an extended period (1890–2009). The findings show remarkable continuity in the choice and proportion of conceptual metaphor across very different sociohistorical contexts. However, this does not correspond to entrenchment of the metaphors which continue to be creative and elaborated in many cases. In terms of variation over time, the analysis shows shifts in framing with greater focus on societal effects and reactions to influenza in later periods while the agency of the virus is reduced.